Transport, mobility, and the production of urban space - Cidell, Julie; Prytherch, David (Routledge studies in human geography, 2015)
pt. I. Intersections : everyday places as nodes -- pt. II. Corridors : links in the network -- pt. III. Networks : cities and regions in wider context -- pt. IV. Circulation : assemblages and experiences of mobility.